Chinese Mothers’ Perceptions of Their Child’s Weight and Obesity Status - Chen, Shu; Binns, Colin; Maycock, Bruce; Zhao, Yun; Liu, Y. (HEC Press, 2014)
This study recorded maternal perceptions of preschool children’s weight in Chinese mothers living in Australia and China. A survey was undertaken of 1951 mothers living in Chengdu and Wuhan, China and 89 Chinese mothers living in Perth, Australia. All participants were mothers with children aged 2-4 years. The children’s weight and height were measured and their weight status were classified using the International Obesity Task Force 2012 revised international child body mass index cut-offs. The prevalence of overweight or obese in children was 16.7% in China and 8% in Australia. The overall percentages of correct maternal perception of the child’s weight were 35% in underweight children, 69.2% in normal weight children but only 10.8% in overweight/obese children. Among the overweight/obese children, only 14% in Australia and 10.8% in China were classified as overweight/obese by their mothers. Within the group of underweight children, normal weight mothers (p=0.004) and mothers with older age children (p=0.015) were more likely to correctly classify children’s weight status. A higher percentage of overweight/obese mothers (p=0.002) and mothers who over-estimated her own weight status (p<0.001) have correct perception of the weight status of their overweight/obese children, compared to their counterparts. There was a high prevalence of incorrect maternal perception of preschool children’s weight status in Chinese mothers, especially those with overweight/obese children. To address the obesity epidemic in children, future health promotion programs should put improved efforts to educate parents about obesity and its health consequences in order to reduce misperceptions.